2015
DOI: 10.1136/annrheumdis-2015-eular.3299
|View full text |Cite
|
Sign up to set email alerts
|

SAT0525 Tocilizumab Compared with Anakinra in Refractory Adult-Onset Still's Disease. Multicenter Study of 75 Patients

Abstract: BackgroundInterleukin (IL)-1 and IL-6 are pivotal cytokines in the pathogenesis of adult-onset Still's disease (AOSD).ObjectivesCompare the efficacy and safety of tocilizumab (TCZ) versus anakinra (ANK) given for at least 1 year to AODS patients refractory to conventional treatment.MethodsMulticenter study (31 hospitals) of 75 patients (TCZ; n=34 and ANK; n 41) with AODS refractory to conventional immunosuppressive drugs and in many cases also to other biological agents.ResultsComparisons of the group of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These articles included 1 RCT [18, 33, 61], 1 post hoc analysis of pooled study results [31], 1 prospective open-label trial [54], 5 nationwide surveys [60, 66, 71, 73, 74], 17 retrospective observational studies or case series [6, 8, 5759, 62–64, 67, 68, 70, 72, 76, 78], 1 meta-analysis [69], and 1 comprehensive review [77]. A total of 60 case reports, mostly related to the use of anakinra were also identified; 7 case reports described the use of canakinumab in AOSD [79–85], and 3 case reports documented the use of rilonacept in AOSD [83, 86, 87]; the complete list of case reports can be viewed in Additional file 1: Table S3 [27, 59, 79134].…”
Section: Resultsmentioning
confidence: 99%
“…These articles included 1 RCT [18, 33, 61], 1 post hoc analysis of pooled study results [31], 1 prospective open-label trial [54], 5 nationwide surveys [60, 66, 71, 73, 74], 17 retrospective observational studies or case series [6, 8, 5759, 62–64, 67, 68, 70, 72, 76, 78], 1 meta-analysis [69], and 1 comprehensive review [77]. A total of 60 case reports, mostly related to the use of anakinra were also identified; 7 case reports described the use of canakinumab in AOSD [79–85], and 3 case reports documented the use of rilonacept in AOSD [83, 86, 87]; the complete list of case reports can be viewed in Additional file 1: Table S3 [27, 59, 79134].…”
Section: Resultsmentioning
confidence: 99%
“…A multi-center comparative study of TCZ with anakinra in patients with refractory to conventional treatment showed TCZ is more efficacious than anakinra [20]. Although the patients in both groups showed similar improvement in clinical parameters, the ESR and CRP levels improved faster in the TCZ group.…”
Section: Discussionmentioning
confidence: 99%
“…Although the patients in both groups showed similar improvement in clinical parameters, the ESR and CRP levels improved faster in the TCZ group. Further, anakinra had to be discontinued in 11 patients (p=0.001) due to inefficacy [20]. Another observational study by Wang, et al included patients with AOSD who have been refractory to steroids and another traditional immunosuppressive agent.…”
Section: Discussionmentioning
confidence: 99%